Analisis Kesulitan Belajar Siswa dalam Pembuatan Pola Busana Menggunakan Teknik Konstruksi di Sekolah Menengah Kejuruan - Nova, Nova Amalia Susanti; Mariah, Siti; Setyaningsih, Rina (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to determine the level of learning difficulties of class X students at SMK Negeri 2 Godean Sleman Yogyakarta in the 2024/2025 Academic Year in making clothing patterns. The population of this study was 102 class X fashion design students. The research sample was 50 students using the Slovin formula. Data collection used a questionnaire via Google Form and documentation. The instrument was tested for validity (product moment) and reliability (Cronbach's alpha). Data were analyzed using descriptive statistics. The results of the study showed that the difficulty of learning to make clothing patterns in the difficult category with a relative frequency of 60.00%, namely: 1) in taking the size of the skirt construction technique is difficult category with a frequency of 42.00%, 2) in making basic skirt patterns using the construction technique is difficult category with a frequency of 58.00%, and 3) in making broken skirt patterns construction technique is very difficult category with a frequency of 78.00%. The conclusion is that the level of learning difficulties of class X students in making clothing patterns using the construction technique is difficult category.